A Link Between Local Enrichment and Scalar Diversity - Sun, Chao; Tian, Ye; Breheny, Richard (Frontiers in Psychology, 2018)
Several recent studies have shown that different scalar terms are liable to give rise to scalar inferences at different rates (Doran et al., 2009, 2012; Van Tiel et al., 2016). A number of potential factors have been explored to account for such Scalar Diversity. These factors can be seen as methodological in origin, or as motivated by the standard Gricean approach to scalar inferences. Such factors allow us to explain some of the variation, but they leave much of it unexplained. In this paper, we explore two new potential factors. One is methodologically motivated, related to the choice of items in previous studies. The second is motivated by theoretical approaches which go beyond the standard Gricean approach to pragmatic effects. In particular, we consider dual route theories which allow for pragmatic inferences to be explained either using ‘global’ pragmatic derivations, like those set out in standard Gricean theory, or using local pragmatic adjustments to interpretation. We focus on one such theory, based on the Bayesian Rational Speech Act approach (RSA-LU, Bergen et al., 2016). We show that RSA-LU predicts that a scalar term’s liability to certain kinds of local enrichment will explain some Scalar Diversity. In three experiments, we show that both proposed factors are active in the Scalar Diversity effect. We conclude that our results provide evidence for such dual route approaches to pragmatic effects.